Effect of preoperative nutritional risk index on 30-day postoperative complications in patients with gastric cancer: a retrospective cohort study - Zou, Yingfeng; Li, Ling; Jia, Kui; Tian, Lei; He, Minying; Huang, Debin (Frontiers in Oncology, 2025)
BackgroundPreoperative nutritional status in patients with gastric cancer after surgery has attracted considerable interest. The nutritional risk index (NRI) has been widely used as a convenient and effective nutritional assessment index, but the relationship between preoperative NRI and postoperative complications in patients with gastric cancer has not been adequately studied. Our study aimed to investigate the effects of preoperative NRI on 30-day postoperative complications in patients with gastric cancer.MethodsThis retrospective analysis investigated 578 patients with gastric cancer. Preoperative NRI calculations were based on serum albumin levels and body weight, and receiver operating characteristic curves were used in analyzing NRI values and establishing optimal cutoff points. Patients were categorized into two groups according to cutoff value: low NRI group (NRI<96.7) and high NRI group (NRI≥96.7). The hazard ratio (HR) for postoperative complications was calculated through Cox regression analysis and adjusted for potential confounders, and the effects of NRI on postoperative complications in patients with gastric cancer were examined. In addition, we conducted subgroup analyses to examine whether there was an interaction between the effect of NRI on the cumulative incidence of postoperative complications and other confounding factors.ResultsOf the 578 patients with gastric cancer who underwent radical surgery, 120 (20.8%) experienced postoperative complications. The optimal NRI threshold of 96.7 was identified using ROC curve analysis. Cox regression analysis demonstrated that preoperative NRI was independently associated with 30-day postoperative complications after adjusting for confounding factors (HR=0.93; 95%CI: 0.90–0.96; P<0.001). Patients in the low NRI group had significantly higher rates of postoperative complications than those in the high NRI group(HR=2.89, 95%CI:1.71–4.88; P<0.001). The cumulative incidence analysis revealed a higher risk of postoperative complications over time in the low NRI group compared with the high NRI group (P<0.001). These associations remained robust in subgroup analyses.ConclusionsNRI is an independent predictor of 30-day postoperative complications in gastric cancer patients and is a convenient and useful nutritional screening tool for identifying patients with gastric cancer at high risk of postoperative complications.